THE AVERAGE ANNUAL EFFECTIVE DOSES FOR THE POPULATION OF THE SETTLEMENTS OF THE RUSSIAN FEDERATION ATTRIBUTED TO ZONES OF RADIOACTIVE CONTAMINATION DUE TO THE CHERNOBYL ACCIDENT (FOR THE ZONATION PURPOSES), 2017 - G. Ya. Bruk; I. K. Romanovich; A. B. Bazyukin; A. A. Bratilova; A. Yu. Vlasov; A. V. Gromov; T. V. Zhesko; M. V. Kaduka; O. S. Kravtsova; K. A. Saprykin; V. S. Stepanov; N. V. Titov; et al. (Радиационная гигиена)
The Chernobyl accident in 1986 is one of the most large-scale radiation accidents in the world. It led to radioactive contamination of large areas in the European part of the Russian Federation and at the neighboring countries. Now, there are more than 4000 settlements with the total population of 1.5 million in the radioactively contaminated areas of the Russian Federation. The Bryansk region is the most intensely contaminated region. For example, the Krasnogorskiy district still has settlements with the level of soil contamination by cesium-137 exceeding 40 Ci/km2. The regions of Tula, Kaluga and Orel are also significantly affected. In addition to these four regions, there are ten more regions with the radioactively contaminated settlements. After the Chernobyl accident, the affected areas were divided into zones of radioactive contamination. The attribution of the settlements to a particular zone is determined by the level of soil contamination with 137Cs and by a value of the average annual effective dose that could be formed in the absence of: 1) active measures for radiation protection, and 2) self-limitation in consumption of the local food products. The main regulatory document on this issue is the Federal law № 1244-1 (dated May, 15 1991) “On the social protection of the citizens who have been exposed to radiation as a result of the accident at the Chernobyl nuclear power plant”. The law extends to the territories, where, since 1991: 1) the average annual effective dose for the population exceeds 1 mSv (the value of effective dose that could be formed in the absence of active radiation protection measures and self-limitation in consumption of the local food products); 2) soil surface contamination with cesium-137 exceeds 1 Ci/km2.The paper presents results of calculations of the average effective doses in 2017. The purpose was to use the dose values (SGED90) in zonation of contaminated territories. Therefore, the calculations have been done under the assumption that the doses were formed in the absence of active radiation protection measures and self-limitation in consumption of the local food products. The dose to population, rather than the density of radioactive contamination of soil by 137Cs, is the most objective characteristic of the actual radiation exposure to the residents of the contaminated areas.